THE IMPACT OF ORGANIZATIONAL RESOURCES ON CUSTOMERS SATISFACTION: Received: 29th November 2021; Revised: 04th December 2021, 23rd December 2021, 6th March 2022; Accepted: 07th March 2022 - Bakatubia, M Sebastian (PEOPLE: International Journal of Social Sciences, 2022)
This study examines how organizational resources and competencies endow the competitive advantage. Often organizations align resources and capabilities to achieve their goal. Drawing on a resource-based view, we come to identify key resources that help the organization execute its business strategy and capture customer satisfaction. In four separate surveys, we firstly identify resources to execute a business plan. We examine those resources in a more elaborate survey to capture the most valuable resources. Further, customers’ satisfaction is also surveyed. Results show that at first customers value organizational resources. Second, when human resources are much clear, customers tend to favour human resources over organizational and physical resources. The implication of this discovery for the organization is also discussed.